The use of S100 proteins testing in juvenile idiopathic arthritis and autoinflammatory diseases in a pediatric clinical setting: a retrospective analysis - Najla Aljaberi; Elena Tronconi; Grant Schulert; Alexei A. Grom; Daniel J. Lovell; Jennifer L. Huggins; Michael Henrickson; Hermine I. Brunner (BMC, 2020)
Abstract Background Serum phagocyte-derived alarmins S100A8/9 and S100A12 are considered useful for the assessment of inflammatory diseases. Our study evaluated the use of S100 proteins in a pediatric clinical setting for estimating disease activity and supporting diagnosis. Methods Patients (n = 136) who had S100 proteins tested as part of clinical care were included in this study and relevant information obtained from the medical record: C-reactive protein (CRP), disease activity status (inactive: = 0 joint; active: > 0 active joint), systemic symptoms in systemic JIA (sJIA), and symptoms of flare of other autoinflammatory and fever syndromes. Patients were categorized as: sJIA, non-systemic JIA (nsJIA), other defined autoinflammatory syndromes (AID) and systemic undifferentiated recurring fever syndromes (SURFS). Results Patients with sJIA (n = 21) had significantly higher levels of S100A8/9 and S100A12 compared to patients with nsJIA (n = 49), other AIDs (n = 8) or SURFS (n = 14) (all p < 0.0001). Compared to CRP [area under the receiver operating characteristics curve (AUC) = 0.7], S100 proteins were superior in differentiating sJIA from AID and SURFS [AUC = 0.9]. S100A8/9 and S100A12 levels were not associated with disease activity in nsJIA, AID or SURFS. S100A8/9 and S100A12 levels were significantly higher in active sJIA compared to inactive (p = 0.0002 and p = 0.0002 respectively). Conclusion Compared to other autoinflammatory and fever syndromes, sJIA patients have markedly higher levels of S100A8/9 and S100A12 proteins which may assist with diagnosis. S100 levels slightly outperformed CRP in distinguishing sJIA from other diagnoses and in sJIA disease activity. S100 proteins may aid in monitoring disease activity in sJIA patients.